Self-determination theory and motivational orientations of Arabic learners: a principal component analysis - Bakar, K.A.; Sulaiman, N.F.; Muhammad Rafaai, Zeti Akhtar (Universiti Kebangsaan Malaysia (UKM), 2010)
Recognizing the value of motivation in language learning, some scholars attempt to gain insights into this abstract psychological state by exploring models of motivation developed by educational and social psychologists. The present study extends an earlier research on motivational orientations for language learning based on the Self- Determination theory. Unlike the previous study which involved the learning of French in a bilingual English-French setting, this study explored the motivational orientations of Muslim learners of Arabic. A 45-item questionnaire was administered to 228 students in a tertiary education institution in Malaysia where Arabic is a requirement. With a total of 28 statistically reliable items, the Intrinsic Motivation-Knowledge, Intrinsic Motivation- Accomplishment, Extrinsic Motivation-Identified Regulation, Amotivation and Religious Motivation components accounted for 64.6% of the variance. Religious motivation emerged as a new statistical subdimension of motivational orientation as Muslim learners in the study showed strong religious motives for learning Arabic, a psychological state which practitioners would want to capitalize on and sustain alongside with other orientations. However, further research needs to be done to study the relationship between the intensity and types of motivational orientations, efforts and learning outcomes, and to compare and contrast the motivational orientations of learners of sacred languages such as Arabic and Hebrew in three different settings: highly religious setting, less religious and non-religious affiliated purposes.